Dynamics of Tactical Radicalisation and Public Receptiveness in Hong Kong's Anti-Extradition Bill Movement. Issue 3 (27th May 2022) - Lee, Francis L. F.; Cheng, Edmund W.; Liang, Hai; Tang, Gary K. Y.; Yuen, Samson
Abstract: The Anti-Extradition Law Amendment Bill (Anti-ELAB) movement in Hong Kong was marked by a significant degree of tactical radicalisation in its first six months. Yet the movement also succeeded in maintaining a high degree of solidarity and public support. This article explains how tactical radicalisation and public receptiveness toward radical actions was achieved. It does this by drawing upon protest onsite survey data, public opinion poll data, analysis of digital media contents and field observations. Theoretically, it combines a relational approach with an emphasis on the role of discursive negotiation. The article first reconstructs the trend of movement radicalisation in Hong Kong since the late 2000s. It then examines the interactional dynamics that drove the process of radicalisation along multiple pathways during the first six months of the Anti-ELAB movement. The articulation of justifications and discursive negotiation of collective restraints is then examined. Overall, the analysis reconstructs the process of stepwise and constrained radicalisation in the Anti-ELAB movement. General theoretical implications of the analysis are discussed.